Space Closure with Different Appointment Intervals: A Split-mouth Randomized Controlled Trial - Hend Salah ElSayed; Amr Ragab El-Beialy; Juan Martin Palomo; Yehya Ahmad Mostafa (Contemporary Clinical Dentistry, 2024)
Background: Canine retraction has been successful with various force systems and retraction techniques. The appointment interval for force reactivation in canine retraction along the archwire is 4–8 weeks. Aims: The aim was to evaluate the effect of different reactivation intervals on the rate of space closure. Settings and Design: This split-mouth randomized clinical trial recruited 38 patients indicated for the first premolar extraction. Methods: Monthly digital models were acquired for 6 months. The first premolars were extracted, and temporary anchorage devices were placed for maximum anchorage control. The canines were retracted using elastomeric chains which were replaced every 2, 4, 6, or 8 weeks. The monthly rate of canine retraction was measured. The time to space closure was calculated. The secondary outcome was the mesial drift of the first molars. Statistical Analysis: The Kaplan–Meier survival analysis and the Friedman test evaluated and compared the groups. Results: There was no significant difference between the monthly canine retraction rate or the first molar mesial drift between the groups. The mean time to space closure was 5.74 months in the 2-week reactivation group, which was statistically less than the other groups. Conclusions: The 2-week reactivation interval may reduce time to space closure. Direct anchorage control with miniscrews limited anchorage loss significantly.